SELF EFFICACY, PENGETAHUAN PAJAK DAN PENGHARGAAN FINANSIAL TERHADAP BERKARIR SEBAGAI KONSULTAN PAJAK PADA MAHASISWA AKUNTANSI UNIVERSITAS MUSLIM INDONESIA - Anita Achmad Payu (Pusat Penerbitan dan Publikasi Ilmiah FEB-UMI, 2024)
ABSTRACt Study aims to examine and test the influence of self-efficacy, tax knowledge, and financial rewards on the career choice of becoming a tax consultant among accounting students at the University of Muslim Indonesia (UMI). The research uses a quantitative approach with primary data collected through questionnaires distributed to accounting students at UMI. The sampling method employed is purposive sampling, and a total of 175 respondents were obtained. The data analysis method used in this study is IBM SPSS Statistics 24 software. The results indicate that self-efficacy, tax knowledge, and financial rewards have a positive and significant impact on the decision to pursue a career as a tax consultant among accounting students at UMI.